Association between wasting and inadequate breastfeeding practices among infants under six months in SNNPR and Somali regions of Ethiopia: A multilevel cross-sectional study - Getachew, Bethel; Berhane, Yemane; Dessie, Yadeta; Yallew, Walelegn W.; Berhane, Hanna Y.; Kim, Sunny S. (2025)
Background Wasting is a severe threat to children’s survival and development. Attaining optimal breastfeeding practices for infants under six months of age remains a significant challenge in low-income countries. This study assessed the association between wasting and breastfeeding practices among infants under six months of age in the SNNPR and Somali regions of Ethiopia.